Hubungan Antara Higiene Sanitasi Terhadap Kontaminasi Telur Cacing Non STH Pada Sayur Lalapan di Warung Makan - Lilik Setyowatiningsih; Ririh Jatmi Wikandari; Surati Surati (Poltekkes Kemenkes Semarang, 2022)
Fresh vegetables can be a source of transmission of worm infections to humans. The behavior of washing fresh vegetables that are not good by housewives and sellers of fresh vegetables in food stalls becomes large in transmitting worm infections if there are worm eggs that are still attached to fresh vegetables. The most common contamination found in fresh vegetables were eggs of the intestinal nematode Soil Transmitted Helminths (STH) as well as non-STH and trematodes. The purpose of this study was to determine the relationship between sanitation hygiene and contamination of non-STH worm eggs in fresh vegetables at food stalls in Semarang City. This type of research is an observational study with a cross sectional approach. Based on the results of laboratory tests, from a total of 165 samples examined, eggs of non-STH worms with species of Fasciola sp and Toxocara sp were found in 45 food stalls selling fresh vegetables. Based on bivariate analysis, there was no significant relationship between personal hygiene (p = 0.071) and environmental sanitation (p = 0.334) on contamination of non-STH worm eggs in fresh vegetables in food stalls in Pedurungan District, Semarang.